1993
DOI: 10.1021/jm00062a017
|View full text |Cite
|
Sign up to set email alerts
|

Application of the hypersurface iterative projection method to bicyclic pyrazolidinone antibacterial agents

Abstract: Bicyclic pyrazolidinones are a class of synthetic antibacterial agents in which the beta-lactam ring is replaced by a five-membered ring. These compounds possess electronic and shape properties required for inhibiting penicillin-binding proteins essential for bacterial cell growth. A novel approach called the hypersurface iterative projection (HIP) method, which is based on three-dimensional computer graphics, allows available structure-activity information to be extrapolated to new synthetic targets. By updat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The stability of 1 is a reflection of the mild electron-withdrawing nature of the C(3) amide group, as mentioned earlier. 18 Although highly soluble, 1 has poor Caco-2 permeability and would not be expected to have oral bioavailability. Stability to both human and CD-1 mouse microsomes is notable with a half-life of >60 min in both preparations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of 1 is a reflection of the mild electron-withdrawing nature of the C(3) amide group, as mentioned earlier. 18 Although highly soluble, 1 has poor Caco-2 permeability and would not be expected to have oral bioavailability. Stability to both human and CD-1 mouse microsomes is notable with a half-life of >60 min in both preparations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…16,17 Broadly, MIC correlates with the electron withdrawing nature of the σ p value of the C(3) substituent and is tunable for reactivity and stability. 14,18 Here, we use only a mildly electron-withdrawing amide group at C(3), which imparts low reactivity and remarkable stability, while simultaneously using the amide to append a siderophore moiety (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Until now, several 1,3-dipoles, such as azomethine ylides (El Ajlaoui et al, 2015), nitrones (Jen et al, 2000;Kano et al, 2005;Suga et al, 2005) and carbonyl ylides (Suga et al, 2007;Nambu et al, 2009;Padwa 2011), have been studied. Among them, N,N 0 -cyclic azomethine imines (Stanovnik et al, 1998;Qiu et al, 2014;Na ´jera et al, 2015;Xu & Doyle, 2014), have been increasingly employed in cycloadditions for the synthesis of pyrazolones and the related dinitrogen-fused heterocyclic derivatives with significant biological activities (Ternansky et al, 1993;Boyd, 1993;Muehlebach, et al, 2009).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Formamide 1 had attracted much interest to characterize its fundamental properties for the last two decades since it is the simplest species containing the amide linkage (–CO–NH–), which is a pharmacophore of the antibacterial agents and designed enzyme inhibitors . Recent reports for organosilicon chemistry showed that silicon substitution can improve bio‐activity of drug derivative by modifying their selectivity, metabolization rate and tissue distribution since silicon slightly differs from carbon in atomic size, electronegativity and lipophilicity .…”
Section: Introductionmentioning
confidence: 99%